Working the spaces of neoliberalism : activism, professionalisation, and incorporation - Laurie, Nina.; Bondi, L. (Liz); Wiley eBooks (Malden, Mass. : Blackwell, 2005)
"Drawing on global research, this book argues that processes of professionalisation form an integral part of the production of neoliberal spaces, with profound implications for political activism. It brings together original research from diverse contexts, including studies conducted in the Global South and the Global North, in order to enable key features of neoliberalisation to be understood more fully."--Jacket.
Introduction / Liz Bondi and Nina Laurie -- 1. After neoliberalism? : community activism and local partnerships in Aotearoa New Zealand / Wendy Larner and David Craig -- 2. Authority and expertise : the professionalisation of international development and the ordering of dissent / Uma Kothari -- 3. Dropping out or signing up? : the professionalisation of youth travel / Kate Simpson -- 4. Ethnodevelopment : social movements, creating experts and professionalising indigenous knowledge in Ecuador / Nina Laurie, Robert Andolina and Sarah Radcliffe -- 5. Working the spaces of neoliberal subjectivity, psychotherapeutic technologies, professionalisation and counseling / Liz Bondi.
Originally published in a special issue of Antipode, 2005.
Includes bibliographical references and index.
Electronic reproduction.
John Wiley and Sons
Keywords: Neoliberalism; Professions -- Social aspects; Social movements; Non-governmental organizations; Political geography; Neoliberalism; Non-governmental organizations; Political geography; Professions -- Social aspects; Social movements; Neoliberalismus; Electronic books